Physics and Applications of High‐β Micro‐ and Nanolasers. Issue 19 (23rd June 2021) - Deng, Hui; Lippi, Gian Luca; Mørk, Jesper; Wiersig, Jan; Reitzenstein, Stephan
Abstract: Micro‐ and nanolasers are emerging optoelectronic components with many properties still to be explored and understood. On the one hand, they make it possible to address fundamental physical questions in the border area between classical physics and quantum physics, on the other hand, they open up new application perspectives in many areas of photonics. This progress report provides an overview of the exciting developments from conventional semiconductor lasers toward nanoscale lasers, whose function relies on increased light–matter interaction in low‐mode‐volume resonators and unconventional gain concepts. The latest advances in the physical understanding of light emission from high‐β lasers, in which a large part of the spontaneous emission is coupled into the laser mode, are highlighted. In the limit of β = 1, this leads to thresholdless lasing and it is shown that quantum optical characterization is required to fully explore the underlying emission processes. In addition, emerging nanolaser concepts based on Fano resonators, topological photonics, and 2D materials are presented. Open questions, future prospects, and application scenarios of high‐β lasers in integrated photonics, quantum nanophotonics, and neuromorphic computing are discussed. Abstract : This progress report provides an overview of the exciting developments from conventional semiconductor lasers to nanoscale lasers, relying on increased light−matter interaction in resonators with low mode volume and unconventional gain concepts. Latest advances in the physical understanding of high‐β lasers are presented, open questions discussed, and their application perspectives in integrated photonics, quantum nanophotonics, and neuromorphic computing highlighted.